2019
DOI: 10.2298/hemind190614027i
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical and biological properties of dental calcium silicate cements - literature review

Abstract: Dental cement materials have been developed with the aim to replace hard dental tissues. The first material used for pulp capping, root canal obturation, bifurcation perforation and apexification is calcium hydroxide (in 1920). A half century later, glass-ionomer cements began to suppress it as dentine substitutes. Finally, in the 1990s, calcium silicate (CS) material appeared in the dental research community as the most promising dentine substitute capable to adequately meet all clinical requirements. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…[ 135 ]. It had the ability to induce differentiation of cells into osteogenic cell lineages due to a property known as osteoinductiveness [ 136 ], which could be due to the release of calcium ions. It was reported that the release of calcium supported the differentiation of dental stem cells and enhanced the biomineralization process [ 137 ].…”
Section: Bioactive Inorganic Materialsmentioning
confidence: 99%
“…[ 135 ]. It had the ability to induce differentiation of cells into osteogenic cell lineages due to a property known as osteoinductiveness [ 136 ], which could be due to the release of calcium ions. It was reported that the release of calcium supported the differentiation of dental stem cells and enhanced the biomineralization process [ 137 ].…”
Section: Bioactive Inorganic Materialsmentioning
confidence: 99%
“…Cement materials in dentistry have been developed to imitate the lost dentine tissue, to mimic biological features as much as possible, and to display bioactive characteristics (Ilić et al, 2019).This is not always simple because of dentine specificity, namely, its close contact with the pulp. In that sense, the local bioactivity of these cement materials is important to induce mineralization within the adjacent dentine (Ilić et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet clinical requirements of CSC based dental material, a radiopacifier has to be added to its composition to allow cement's visibility on radiographs 2,8,9 . However, finding an ideal balance between the ratio of radiopacifier and cement powder remains a challenge of the dental and engineering community 3,10,11 . When choosing a proper radiopacifier for cement fabrication several aspects should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%